Photonics-based radio frequency amplification in radio over fiber systems with CAP modulation - Estrada, Natalia Ca?as (2015)
The objective of this work is the implementation of a radio-frequency (RF) amplifier based on the four-wave mixing nonlinear effect applied to a radio over fiber (RoF) system with CAP (Carrierless Amplitude Phase modulation). Such system enables the transmission of information using an optical backhaul, wherein the optical fiber is used as the communication channel and as an active medium for RF gain. The RF gain is defined as the difference between the photodetected electrical power in the FWM product and that of the conventional RoF system. This gain strongly depends on the electrical and optical parameters of the system, such as separation of lasers, state of the light polarization, frequency of the RF carrier and the bias voltage of the optical modulator. The work is based on numerical simulations using OptiSystem ?, by Optiwave Inc., and experimental results obtained in cooperation with the Lasor laboratory from the research and development center (CPqD) of Campinas-SP, Brazil. Experiments results demonstrate photonics-based RF amplification from 4.0 to 19.0 GHz, signal-to-noise ratio (SNR) up to 51 dB and electrical gains up to 26 dB.